Bio-efficacy and post harvest residual toxicity of new fungicides against sheath blight (Rhizoctonia solani) of rice (Oryza sativa) - KUMAR, PANKAJ; AHLAWAT, SUSHIL; CHAUHAN, REENA; KUMAR, ANIL; SINGH, RAM; KUMAR, ASHWANI (The Indian Journal of Agricultural Sciences, 2018)
Four new fungicidal formulations, viz. tebuconazole 50% + trifloxystrobin 25% WG, difenoconazole 25% SC, propiconazole 13.9% + difenconazole 13.9% EC and kresoxim methyl 44.3% SC were evaluated against Rhizoctonia solani Kuhn of rice (Oryza sativa L.) in vitro and under field conditions during kharif 2016 and 2017. In vitro growth inhibition tests revealed that the EC50 values of tebuconazole 50% + trifloxystrobin 25% WG, difenoconazole 25% SC, propiconazole 13.9% + difenconazole 13.9% EC and kresoxim methyl 44.3% SC against R. solani ranged from 0.398 o 42.35 ppm a.i., whereas the corresponding EC90 values were 8.92 to more than 2000 ppm a.i. Tebuconazole 50% + trifloxystrobin 25% WG was most inhibitory to mycelial growth of the fungus with EC50 and EC90 values of 0.39 and 8.92 ppm a.i. followed by propiconazole 13.9% + difenconazole 13.9% EC. Tebuconazole 50% + trifloxystrobin 25% WG and propiconazole 13.9% + difenconazole 13.9% EC completely inhibited the sclerotia formation at 2.5 ppm and 25 ppm a.i., respectively. In field trials, tebuconazole 50% + trifloxystrobin 25% WG sprayed at 0.4 and 0.8 g/l proved most effective and suppressed sheath blight severity by 50.98 and 79.12%, respectively along with enhancing grain yield of rice followed by propiconazole 13.9% + difenconazole 13.9% EC. However, kresoxim methyl 44.3% SC was the least effective fungicide. Based on bioefficacy and benefit-cost ratio, spray application of tebuconazole 50% + trifloxystrobin 25% WG at 0.4 g/l and propiconazole 13.9% + difenconazole 13.9% EC at 2 ml/l were found highly economical in managing sheath blight of rice with a benefit-cost of 3.52 and 3.02, respectively. Post harvest residues analysis of tebuconazole 50% + trifloxystrobin 25% WG, propiconazole 13.9% + difenconazole 13.9% EC and difenoconazole 25% SC were found below limit of quantification, i.e. 0.01 ppm in rice grains, cropped soil, paddy straw and husk at their single/recommended and double of the recommended doses indicating that tebuconazole 50% + trifloxystrobin 25% WG at 0.4 g/l and propiconazole 13.9% + difenconazole 13.9% EC were safe from the human, animals and environmental point of view.